Acid‐Ionizable Iron Nanoadjuvant Augments STING Activation for Personalized Vaccination Immunotherapy of Cancer. Issue 10 (10th January 2023) - Chen, Fangmin; Li, Tianliang; Zhang, Huijuan; Saeed, Madiha; Liu, Xiaoying; Huang, Lujia; Wang, Xiyuan; Gao, Jing; Hou, Bo; Lai, Yi; Ding, Chunyong; Xu, Zhiai; et al.
Abstract: The critical challenge for cancer vaccine‐induced T‐cell immunity is the sustained activation of antigen cross‐presentation in antigen‐presenting cells (APCs) with innate immune stimulation. In this study, it is first discovered that the clinically used magnetic contrast agents, iron oxide nanoparticles (IONPs), markedly augment the type‐I interferon (IFN‐I) production profile of the stimulator of interferon genes (STING) agonist MSA‐2 and achieve a 16‐fold dosage‐sparing effect in the human STING haplotype. Acid‐ionizable copolymers are coassembled with IONPs and MSA‐2 into iron nanoadjuvants to concentrate STING activation in the draining lymph nodes. The top candidate iron nanoadjuvant (PEIM) efficiently delivers the model antigen ovalbumin (OVA) to CD169+ APCs and facilitates antigen cross‐presentation to elicit a 55‐fold greater frequency of antigen‐specific CD8 + cytotoxic T‐lymphocyte response than soluble antigen. PEIM@OVA nanovaccine immunization induces potent and durable antitumor immunity to prevent tumor lung metastasis and eliminate established tumors. Moreover, PEIM nanoadjuvant is applicable to deliver autologous tumor antigen and synergizes with immune checkpoint blockade therapy for prevention of postoperative tumor recurrence and distant metastasis in B16‐OVA melanoma and MC38 colorectal tumor models. The acid‐ionizable iron nanoadjuvant offers a generalizable and readily translatable strategy to augment STING cascade activation and antigen cross‐presentation for personalized cancer vaccination immunotherapy. Abstract : An acid‐ionizable iron nanoadjuvant (PEIM) is developed to potentiate cancer vaccination immunotherapy. PEIM nanoadjuvant is coassembled from acid‐ionizable copolymers with iron oxide nanoparticles (IONPs) and a stimulator of interferon genes (STING) agonist. PEIM nanoadjuvant effectively delivers tumor antigens to lymph nodes, amplifies STING activation and type‐I interferon (IFN‐I) production, and ultimately elicits antigen‐specific T‐cell response to inhibit tumor growth.